2023
DOI: 10.1101/2023.06.02.23290905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial Differences in Associations Between Adverse Childhood Experiences and Physical, Mental, and Behavioral Health

Abstract: Introduction: Adverse childhood experiences (ACEs) are associated with poor adulthood health, with individuals experiencing multiple ACEs at greatest risk. Multiracial people have high mean ACEs scores and elevated risk of several outcomes, but are infrequently the focus of health equity research. This study aimed to determine whether this group should be targeted for prevention efforts. Methods: We analyzed Waves 1 (1994-95), 3 (2001-02), and 4 (2008-09) of the National Longitudinal Study of Adolescent to Adu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…16,17 Multiple studies have found that Multiracial -those identifying with more than one racial groupand AI/NA people consistently report the highest number of ACEs of all race/ethnicities. 6,9,[18][19][20][21] However, small population sizes and inconsistency of racial data collection instruments mean that such population health analyses infrequently focus on Multiracial and AI/NA groups. As described above, there is a clear connection between colonialist land occupation, structural racism, and ACEs for the AI/NA population.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Multiple studies have found that Multiracial -those identifying with more than one racial groupand AI/NA people consistently report the highest number of ACEs of all race/ethnicities. 6,9,[18][19][20][21] However, small population sizes and inconsistency of racial data collection instruments mean that such population health analyses infrequently focus on Multiracial and AI/NA groups. As described above, there is a clear connection between colonialist land occupation, structural racism, and ACEs for the AI/NA population.…”
Section: Introductionmentioning
confidence: 99%